1966
DOI: 10.1111/j.2517-6161.1966.tb00631.x
|View full text |Cite
|
Sign up to set email alerts
|

A Test for “Intrinsic Correlation” in the Theory of Accident Proneness

Abstract: Summary We consider a model in accident theory which is a modified version of the one proposed and studied by Bates and Neyman (1952a). The model envisages a correlation between the two kinds of accident in the model of Bates and Neyman. We set up a test of significance that this correlation is zero. Some properties of the distribution arising from the modified approach are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Our model generalizes this idea in the sense that we start from a bivariate model while their model was based on two independent Poisson distributions. Following the terminology of Subrahmaniam (1966), our model assumes intrinsic correlation as well (measured by θ 3 ) and thus it is much more general. Our advance is that we also assume a multivariate prior allowing for correlation between the parameters but in our case the posterior can be obtained in closed form without the need of MCMC or approximations.…”
Section: Discussionmentioning
confidence: 99%
“…Our model generalizes this idea in the sense that we start from a bivariate model while their model was based on two independent Poisson distributions. Following the terminology of Subrahmaniam (1966), our model assumes intrinsic correlation as well (measured by θ 3 ) and thus it is much more general. Our advance is that we also assume a multivariate prior allowing for correlation between the parameters but in our case the posterior can be obtained in closed form without the need of MCMC or approximations.…”
Section: Discussionmentioning
confidence: 99%
“…(i) Bivariate Negative Binomial Edwards and Gurland (1961) and Subrahmaniam (1966) have independently developed the generalized version of the Bates-Neyman model. Here ~ is taken to have the two parameter gamma distribution with pdf…”
Section: Examplesmentioning
confidence: 99%
“…This is given by: Subrahmaniam (1966) has shown that the generating function is given by In the particular cases we study below, the r.v. Y2 will be seen to be a convolution itself.…”
Section: Recurrence Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the use of bivariate negative binomial (BNB) distribution is a sound alternative. In fact, Subrahmaniam [5] and Subrahmaniam and Subrahmaniam [6] suggested a BNB distribution that is obtained from a gamma mixture of a BP distribution. Other types of BNB distributions were suggested by [7], who proposed the BNB distributions using a gamma mixture of two independent Poisson distributions, and Lee and Ong [8], who used the trivariate reduction technique from three independent negative binomial (NB) random variables.…”
Section: Introductionmentioning
confidence: 97%